Adaptive Regulation in Optimizing Csr “Bulog Peduli Umk” To Improve Food Security on Buru Island - Hukunala, Sandy Victor; Hetharie, Jondry Adrin (Law and Economics, 2025)
Food security in Indonesia's remote island regions (3T) remains a critical challenge, often exacerbated by ineffective Corporate Social Responsibility (CSR) programs run by state-owned enterprises (SOEs). The main problem lies in the rigid and uniform (“one size fits all”) regulatory framework that fails to adapt to the unique socio-economic realities and infrastructure in these areas, thereby hampering efforts to support local food supply chains. This article aims to formulate an adaptive regulatory model to optimize the “Bulog Peduli UMK” CSR program in improving food security in 3T island regions such as Buru Island. The problem focuses on the fundamental weaknesses of the centralistic and “one size fits all” regulatory framework for SOE CSR, as well as the weak mandate for cross-sector coordination, which has led to ineffective program implementation in the field. To address these issues, a legal-empirical approach is used with a conceptual framework of adaptive regulation to bridge the gap between the ideal conditions (das sollen) and the reality in the field (das sein). Data was collected through regulatory studies, in-depth interviews with stakeholders (Bulog, local government, MSMEs), and surveys in Buru and South Buru Regencies, then analyzed normatively-qualitatively and descriptively-qualitatively. This study concludes that the implementation of the program is dualistic: effective in terms of ease of access to initial capital (85%), but failing in terms of supply stability (35%) and training relevance (40%). Therefore, an adaptive regulatory model based on four pillars (decentralization, mandatory partnerships, sustainable schemes, and contextual digitalization) is needed to transform CSR from an assistance program into an integrated regional development instrument. Theoretically, this study presents a new conceptual framework for SOE CSR in 3T regions, while in practical terms, the proposed model offers policy recommendations that can be followed up by the government and SOEs to improve program effectiveness and food security impacts